Chlorophyll and morphological mutants of black gram (Vigna mungo (L.) Hepper) derived by gamma rays and EMS - L. Mullainathan, D. Arulbalachandran (Journal of Phytology, 2009)
Micro and macro-mutants play an important role to assess the dose/concentration of mutagens. In the present investigation, some of the chlorophyll mutants were observed in the different dose/concentrations of gamma rays they were chlorina albino, xantha, and viridis. Among the mutagens, Morphological mutants were observed in M2 generation with effect of dose/concentration of mutagens and such mutants were,Ã‚Â  dwarf, tall, tiny leaves, hairy leaves, male sterility, brown seed, early, maturing, long pod, bottom branching, top branching, bushy type, trailing and spreading habit mutants were observed in M2 generation. Mutant and its derivatives when used in cross breeding have found to be more productive in the development of improved varieties of black gram. EMS provided more number of chlorophyll and morphological mutants followed by gamma rays in this investigation.